(untitled) (Research, Society and Development, 2021)
Biotechnology is the branch of science that uses molecules, viruses, microorganisms, cells, animals, plants or part of them in technological processes to generate benefits for humans, to flora, fauna and the environment. In this context, enzymes are natural biocatalysts that present substrate specificity and extreme importance to vital processes, as they develop indispensable functions in biochemical reactions of cell metabolism, and can be used in biotechnological processes. Knowing the human needs, for a world population of about 7.7 billion people and the functional usefulness of enzymes, there is, on the one hand, a gigantic demand for the consumption of various products in the agricultural sector, processed and industrialized, such as: food, beverages, clothing in the textile sector, medicines, vaccines, cosmetics in the chemical-pharmaceutical sector, as well as in the production of paper and fuels, in which enzymes, mainly amylases, have been widely used in production processes. In this work, experiments were carried out with the wild Bacillus cereus bacterium to verify the production of amylases, the results obtained could demonstrate the formation of amylolysis halos around the colonies in Petri dishes containing Tryptic Soy Agar + starch (1%) medium, pH 7.3 and grown in a biological oven at 37oC for 24 hours, when revealed in iodine vapor; the Amylolysis Index (AI) was 3.3 and the efficiency of starch substrate degradation by amylases was greater than 90% in the evaluated treatments.